Paper-Based Sensors: Fantasy or Reality? - Ghenadii Korotcenkov (Nanomaterials)
This article analyzes the prospects for the appearance of paper-based sensors on the sensor market. It is concluded that paper-based sensors are not a fantasy but a reality. It is shown that paper has properties that make it possible to develop a wide variety of paper-based sensors, such as SERS, colorimetric, fluorescent, conductometric, capacitive, fiber-optic, electrochemical, microfluidic, shape-deformation, microwave, and various physical sensors. The use of paper in the manufacturing of various sensors opens up new possibilities both in terms of new approaches to their manufacturing and in terms of new areas of their application. However, it must be recognized that for the widespread use of paper and the appearance of paper-based sensors on the sensor market, many obstacles must be overcome.